2020
DOI: 10.1002/fut.22096
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oil price shocks on asset markets: Evidence from oil inventory news

Abstract: We quantify the reaction of U.S. equity, bond futures, and exchange rate returns to oil price shocks driven by oil inventory news. Across most sectors, equity prices decrease in response to higher oil prices before the 2007/2008 crisis but increase after it. Positive oil price shocks cause a depreciation of the U.S. dollar against a broad range of currencies but have only a modest effect on bond futures returns. The evidence suggests that changes in risk premia help to explain the time‐varying effect of oil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Topics include price discovery in commodities (Schwarz & Szakmary, 2010; Yang et al, 2001), the relationship between spot and futures prices of commodities (Silvapulle & Moosa, 1999), the relationship between volatility and price of commodities (Pindyck, 2004), and the determinants of volatility in commodity prices (Ball et al, 1985). Other topics include forecasting of commodity prices (Grudnitski & Osburn, 1993), liquidity in commodity markets (Cho et al, 2019), the predictive abilities of speculators in commodity markets (Merkoulova, 2020), the effect of oil shocks on the asset market (Alquist et al, 2020), and the relationship between commodity risk and economic growth (Kang & Kwon, 2020). Considering JFM's focus on futures markets, having commodities as its largest thematic cluster comes as no surprise.…”
Section: Bibliographic Coupling Of Jfm Articlesmentioning
confidence: 99%
“…Topics include price discovery in commodities (Schwarz & Szakmary, 2010; Yang et al, 2001), the relationship between spot and futures prices of commodities (Silvapulle & Moosa, 1999), the relationship between volatility and price of commodities (Pindyck, 2004), and the determinants of volatility in commodity prices (Ball et al, 1985). Other topics include forecasting of commodity prices (Grudnitski & Osburn, 1993), liquidity in commodity markets (Cho et al, 2019), the predictive abilities of speculators in commodity markets (Merkoulova, 2020), the effect of oil shocks on the asset market (Alquist et al, 2020), and the relationship between commodity risk and economic growth (Kang & Kwon, 2020). Considering JFM's focus on futures markets, having commodities as its largest thematic cluster comes as no surprise.…”
Section: Bibliographic Coupling Of Jfm Articlesmentioning
confidence: 99%
“…The dependence structure between the oil and stock markets is dynamic in different market states (Alquist et al, 2020; Bampinas & Panagiotidis, 2017; Wen et al, 2012; Zhang & Liu, 2018). During financial crises, herding behavior heightens and the impacts of changes in macroeconomic factors are elevated, resulting in a higher probability of joint extreme losses for the oil and stock markets and increased dependence between them (Aloui et al, 2013).…”
Section: Data and Hypothesis Developmentmentioning
confidence: 99%
“…Earlier studies often suggest a negative relationship by observing that high oil prices typically lead to stock price crashes (Sim & Zhou, 2015). However, empirical studies have also found a positive relationship (Mensi et al, 2017) and a contingent relationship depending on the cause of oil price shock (Mokni, 2020; Wong, 2021) and market status (Alquist et al, 2020). These mixed and contradictory results are at least partially due to the weakness of financial contagion detection methods used in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increasing trade among different nations and the globalization of financial markets has also contributed to the connectedness among cross‐border commodity markets (Yang & Zhou, 2020 ). Under the influence of a strong external shock, such interdependence between different international commodity markets could accelerate risk spillover (Alquist et al, 2020 ; Melvin & Sultan, 1990 ; Song et al, 2018 ; Webb et al, 2016 ), which might lead to extreme events, such as negative oil futures prices at the start of the COVID‐19 pandemic in the spring of 2020 and cross‐broader supply chain disruption due to the pandemic lockdown. Thus, understanding the international linkages of commodity futures markets could help regulators to stabilize the global commodity supply chain.…”
Section: Introductionmentioning
confidence: 99%